Effect of the Concentration of Carboxy Methyl Cellulose and Tapioka Flour on Organoleptic Fruit Leather Mesocarp of Lontar Fruit (Borassus flabellifer) - Sutiono Sutiono; Ida Agustini Saidi; Rima Azara (jurnal makanan tropis dan teknologi agroindustri, 2022)
This study aims to determine the effect of the concentration of Carboxy Methyl Cellulose, Tapioca Flour on the Characteristics of the Fruit Leather Mesocarp of Lontar Friut (Borassus flabellifer). The design in this study was a one-factor randomized block design (RAK), wich consisted of 10 treatments, namely (CM1), (CM2), (CM3), (CM4), (CM5), (TP1), (TP2), (TP3 ), (TP4), (TP5). Analysis using ANOVA and 5% BNJ follow-up test. The results showed that the concentration of Caboxy Methyl Cellulose, Tapioca Flour Fruit Leather Mesocarp Lontar Fruit (Borassus flabellifer), had a very significant effect on the characteristics of water content, color characteristics (lightness, greeness, yellowness), organoleptic characteristics of color, aroma, taste, texture, characteristics. physical value of texture (hardness, cohesiveness, adhesiveness, chewiness and gummyness). The best treatment is CM5 which shows the value of water content 9.13%, lightness value 51.52, greenness 8.72, yellowness 16.54, physical texture value (hardness 662.73 g, cohesiveness 0.98, adhesiveness 5.54 mJ , springiness 1.0 mm, chewiness 14.37 mJ and gumminess 432.83 g), and color organoleptic value 6.23, aroma 6.67 texture 5.57, taste 3.77.